Effects and Non-Effects of Late Language Exposure on Spatial Language Development: Evidence from Deaf Adults and Children. Issue 1 (2nd January 2021) - Karadöller, Dilay Z.; Sümer, Beyza; Özyürek, Aslı
ABSTRACT: Late exposure to the first language, as in the case of deaf children with hearing parents, hinders the production of linguistic expressions, even in adulthood. Less is known about the development of language soon after language exposure and if late exposure hinders all domains of language in children and adults. We compared late signing adults and children (MAge = 8;5) 2 years after exposure to sign language, to their age-matched native signing peers in expressions of two types of locative relations that are acquired in certain cognitive-developmental order: view-independent (IN-ON-UNDER) and view-dependent (LEFT-RIGHT). Late signing children and adults differed from native signers in their use of linguistic devices for view-dependent relations but not for view-independent relations. These effects were also modulated by the morphological complexity. Hindering effects of late language exposure on the development of language in children and adults are not absolute but are modulated by cognitive and linguistic complexity.